The Effect of Amphidromus palaceus and Lissachatina fulica land snail mucus on collagen density in white rats (Rattus norvegicus) - Pertiwi, Meilisha Putri; Juliandi, Berry; Nurinsiyah, Ayu Savitri; Priawandiputra, Windra; Iskandar, Johan (Biota, 2025)
Treatment with natural ingredients is essential for healing incision wounds. One promising natural remedy is land snail mucus, which has been used for centuries to address various health conditions, including wounds. This study aimed to evaluate the effects of mucus from Amphidromus palaceus and Lissachatina fulica on collagen density during the healing process of incision wounds in Rattus norvegicus. The in vivo study included 36 rats, divided into four cages with nine rats per cage. Each of rats subjected to approximately 1 cm incision wounds on their backs. The rats were divided into four groups: a negative control group (KN) receiving aquades, a positive control group (KP) treated with 1% bioplacenton, treatment group 1 (P1) receiving 25 µL of A. palaceus mucus, and treatment group 2 (P2) receiving 25 µL of L. fulica mucus. The experiment concluded on days H3, H5, H7, and H10. Histological preparations were made using MT staining to assess collagen density. The results showed both species of snail mucus significantly increased collagen density compared to the negative control (aquades). However, there were no statistically significant differences when comparing L. fulica, A. palaceus, and bioplacenton. Among all the treatment groups, L. fulica mucus (P2) produced the highest collagen density. These findings suggest that both types of snail mucus hold promising potential in promoting the wound healing process.